Draft Seventh Five Year Plan 1985-90 and Draft Annual Plan 1985-86 Scheme Wise Details Volume I (Sectors: 1-Agriculture to 22-Environmental Programme) Union Territory of Pondicherry - Planning Commission (Planning Commission, 1985)
The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, Karaikal, Mahe and Yanam lying geographically isolated from one another. Pondicherry region which is on the east coast, about 160 kms. south of Madras is the largest of these and consists of 12 scattered areas interspersed with enclaves of South Arcot District of Tamil Nadu. Karaikal region is about 140 kms. south of Pondicherry and it is surrounded by Thanjavur District of Tamil Nadu. Yanam region is located about 650 kms. north of Madras near Kakinada in Andhra Pradesh. Mahe region is on the west/about 160 kms. south of Mangalore in Kerala.
Government of Pondicherry, Planning and Research Department